ASSESSMENT OF THE CYBERSECURITY RISKS OF THE INTERNET OF THINGS SYSTEM BASED ON ARCHITECTURE MODEL CLOUD SERVICES AND SELECTION PARAMETRIES VULNERABILITIES OPEN BASES (Modern information system and technologies, 2018)
The growth in the number of devices with the ability to connect to the global network caused the need for their combination in a plurality. This allowed to centralize the management, monitoring and maintenance, as well as to expand the functionality of the established Internet of Things system. On the other hand, the devices of such systems are attack objects, which makes it necessary to model the risks of cybersecurity at the design stage.